Peranan Kepolisian Dalam Menanggulangi Pungutan Liar Terhadap Sopir Truk Pengolah Kelapa Sawit Oleh Warga Masyarakat Di Wilayah Hukum Kepolisian Resor Kuantan Singingi - Epri Naldi Lendri; Mexsasai Indra; Ferawati ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Illegal charges are acts committed by someone or more by requesting payment of an unsuitable amount of money or not under the rules relating to the payment. Factors that influence the occurrence of illegal charges are: abuse of authority of position or power, mental character or behavior, cultural or organizational culture, limited human resources, and weakness of control system and supervision. Illegal levies need to be prevented and eradicated because of the impact that has caused public comfort and peace to be disturbed. Police especially the Kuantan Singingi Police Force as state apparatus that carries out the functions of law enforcement, security, and public, order and protection, security and public servant, must perform all these functions in order to provide a sense of security and comfort to the people, especially Kuantan Singingi people.This type of research can be classified in the type of sociological legal research, the approach by looking in terms of reality the occurred in the field and provide acomplete and clear picture of the problem under study. The research was conducted in the jurisdiction of the Kuantan Singingi Police Resort. While the population and sample are all parties used, primary data, secondary data, consisting of primary, secondary, and tertiary legal materials, data colection techniques in this study with observation, questionnaire, interview, and literature review.From the results of research problems there are two main things that can be concluded. First, in tackling the practice of illegal levies, especially on the highway Police Resort Kuantan Singingi have made various efforts or have taken legal action in which the role of Police as follows patrolling the region, forming saber pungli team, giving severe punishment to perpetrators/illegal fees, and socialize to the community about illegal levies and punisment. Second, the factors that hampered the police force of the Kuantan Singingi Resort in tackling the illegal levies on truck drivers of palm oil trucking by the community are: lack of human resources, lack of legal institusions, limited Police facilities and infrstructure, and lack of public awareness of the law itself the author’s suggestion, first: in tackling the practice of this illegal levy the Police should better maximize existing efforts and coordinate white each other. Secondly: it is expected that the police add operational funds and the number of personel, increase sozialization to the community, then add equip facilities and infrastructure.Keywords: Role – Police – Tackle – Illegal charges